Extraction of anglicisms from a corpus of Macedonian magazine texts - Miloshevska, Lina (English Studies at NBU, 2025)
The present article is a description of the stages involved in compiling a specialized corpus of Macedonian magazine texts and the software tools employed to extract anglicisms from the corpus. The texts were collected from the magazine Kapital and cover two distinct periods: the years 2000 and 2020. The size of the corpus is about 2 million tokens and 141,852 types. The software employed produced word lists that later in combination with other statistical techniques produced a refined Anglicism headword list from which new anglicisms were extracted. In addition to the software tools, careful manual inspection was necessary in both the extraction and analysis stages. As a result of the research, a total of 220 completely new anglicisms have been identified. Most of these new anglicisms are not yet included in existing Macedonian dictionaries.